2023
DOI: 10.3390/w15091706
|View full text |Cite
|
Sign up to set email alerts
|

Reflection Spectra Coupling Analysis and Polarized Modeling of Optically Active Particles in Lakes

Abstract: The coupling between optically active substances of algae particles and inorganic suspended solids of water makes the characteristics of reflection spectra of water complex and changeable. This makes modeling and inversion of polarization remote sensing in class II water difficult. In our study, considering the influence of the mixing ratio of algae particles and inorganic suspended solids, the sensor incidence angle, and the solar zenith angle on the polarization reflection spectrum, we analyzed the coupling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…The results indicated that a small amount of antisolvent could be well dispersed in the perovskite precursor. , However, particle size in dynamic light scattering (DLS) measurement (Figure a) gradually grew from 200–300 nm (control precursor) to 300–2000 nm (precursor with IPA additive). The precursors with EA and CB additives also showed larger particle sizes than the control, which indicates the growth of particle under different antisolvent additives. , In addition, there is an observable peak at about 1 nm in Figure a, which indicates that there are smaller clusters in the precursor, and the formation of smaller clusters may be caused by the distribution of residual antisolvents and the dissolution of larger colloidal particles. The ultraviolet–visible (UV–vis) reflectance spectrum of the antisolvent-added precursor was higher than that of the reference precursor (Figure b), indicating the presence of perovskite seeds increased light reflection; the higher the seed concentration, the larger the volume and the stronger the reflectivity. , The seeds act as nucleation sites in the film formation process. The residual antisolvent promotes solvent volatilization, accelerating the formation of supersaturated state in the initial spin coating process. , …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The results indicated that a small amount of antisolvent could be well dispersed in the perovskite precursor. , However, particle size in dynamic light scattering (DLS) measurement (Figure a) gradually grew from 200–300 nm (control precursor) to 300–2000 nm (precursor with IPA additive). The precursors with EA and CB additives also showed larger particle sizes than the control, which indicates the growth of particle under different antisolvent additives. , In addition, there is an observable peak at about 1 nm in Figure a, which indicates that there are smaller clusters in the precursor, and the formation of smaller clusters may be caused by the distribution of residual antisolvents and the dissolution of larger colloidal particles. The ultraviolet–visible (UV–vis) reflectance spectrum of the antisolvent-added precursor was higher than that of the reference precursor (Figure b), indicating the presence of perovskite seeds increased light reflection; the higher the seed concentration, the larger the volume and the stronger the reflectivity. , The seeds act as nucleation sites in the film formation process. The residual antisolvent promotes solvent volatilization, accelerating the formation of supersaturated state in the initial spin coating process. , …”
Section: Resultsmentioning
confidence: 98%
“…29−31 The ultraviolet−visible (UV−vis) reflectance spectrum of the antisolvent-added precursor was higher than that of the reference precursor (Figure 1b), indicating the presence of perovskite seeds increased light reflection; the higher the seed concentration, the larger the volume and the stronger the reflectivity. 32,33 The seeds act as nucleation sites in the film formation process. The residual antisolvent promotes solvent volatilization, accelerating the formation of supersaturated state in the initial spin coating process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%